Age and Gender Differences in Emotion Recognition - Abbruzzese, Laura; Magnani, Nadia; Robertson, Ian H.; Mancuso, Mauro (Frontiers in Psychology, 2019)
Background: Existing literature suggests that age affects recognition of affective facial expressions. Eye-tracking studies highlighted that age-related differences in recognition of emotions could be explained by different face exploration patterns due to attentional impairment. Gender also seems to play a role in recognition of emotions. Unfortunately, little is known about the differences in emotion perception abilities across lifespans for men and women, even if females show more ability from infancy. Objective: The present study aimed to examine the role of age and gender on facial emotion recognition in relation to neuropsychological functions and face exploration strategies. We also aimed to explore the associations between emotion recognition and quality of life. Methods: 60 healthy people were consecutively enrolled in the study and divided into two groups: Younger Adults and Older Adults. Participants were assessed for: emotion recognition, attention abilities, frontal functioning, memory functioning and quality of life satisfaction. During the execution of the emotion recognition test using the Pictures of Facial Affects (PoFA) and a modified version of PoFA (M-PoFA), subject’s eye movements were recorded with an Eye Tracker. Results: Significant differences between younger and older adults were detected for fear recognition when adjusted for cognitive functioning and eye-gaze fixations characteristics. Adjusted means of fear recognition were significantly higher in the younger group than in the older group. With regard to gender’s effects, old females recognized identical pairs of emotions better than old males. Considering the Satisfaction Profile we detected negative correlations between some dimensions (Physical functioning, Sleep/feeding/free time) and emotion recognition (i.e. sadness, and disgust). Conclusion: The current study provided novel insights into the specific mechanisms that may explain differences in emotion recognition, examining how age and gender differences can be outlined by cognitive functioning and face exploration strategies.